Morphological and Functional Assessment of Human Fetal Liver Cells in Long-Term Culture - Todorov, P.; Konakchieva, R.; Dimitrov, J.; Novachkov, V.; Kyurkchiev, D.; Drokin, S. I.; Gorokhova, N. A. (Problems of Cryobiology and Cryomedicine, 2006)
Morphology and behavior of human fetal liver cells (hFLCs) during culture were investigated. The adherent fraction of fetal liver cells was found to posses a good proliferative activity. Light end electron microscopic assesment showed the large nucleus size and the poor content of cytoplasm organelles evidenced the low differentiation status of the cell culture. In this respect immunophenotypic analysis was carried out and low expression of HLA-DR, CD13 and CD45 was determined. The data obtained by flow cytometry revealed poor content of differentiated and antigen-presenting cells in the examined cultures of hFLCs.